If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + z)(-6) = 120 Reorder the terms for easier multiplication: -6(3 + z) = 120 (3 * -6 + z * -6) = 120 (-18 + -6z) = 120 Solving -18 + -6z = 120 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -6z = 120 + 18 Combine like terms: -18 + 18 = 0 0 + -6z = 120 + 18 -6z = 120 + 18 Combine like terms: 120 + 18 = 138 -6z = 138 Divide each side by '-6'. z = -23 Simplifying z = -23
| -4+.41m=45.2 | | 27z+21=22-4z | | 162x+4=-2x | | -34=6m+-4 | | g-4.7=5.91 | | 4x-3-x=-x+15 | | 26x+4=17 | | 9v-8=10 | | 5b+11=556-4b | | 15f+9=3(15f+3) | | 1725-115m=460 | | 3x-4=1x+5 | | 4x+2=6-4x | | 2p-2=6 | | 1725+115m=460 | | 14=3y-7 | | 48+48=x | | (2+3i)(4-i)=0 | | -6(7v-5)-3=3(v-6) | | -17=19-12m | | 4x+6=5x-12 | | X+4.5=8.7 | | 0.2x+3=28 | | 1.3+x=-1.6 | | V+6=-12 | | S=52+2.75p | | -1+3(x+2)=5(1+8x) | | -(2y-12+(-y))=-33 | | Y^4+y^3-4y-16=0 | | 5x+12=108-10x | | 1.3+-1.6= | | (4x)-(3x)+(2x)=24 |